Kerjasama Orang Tua dengan Guru dalam Pembentukan Karakter Religius Peserta Didik di SMK Negeri 1 Salatiga - Laksono, Kabul; Nursikin, Mukh (Lembaga Yasin AlSys, 2022)
This study focuses and aims to find out the forms of cooperation between teachers and parents, find out the supporting and inhibiting factors in carrying out the formation of religious character in students at SMK N 1 Salatiga, the method used in this study uses descriptive qualitative methods, to data collection methods in this research using observation, interviews, and documentation. For samples taken from the results of interviews with school principals, curriculum assistants, PAI teachers, homeroom teachers, parents as informants and some documentation as supporting data. These findings indicate that to carry out the formation of student character several supporting activities can be carried out, and require close relationships between teachers at school and parents at home.